Development of β-Amino Alcohol Derivatives that Inhibit Toll-Like Receptor 4 Mediated Inflammatory Response as Potential Antiseptics - Chavez, Sherry A. (2011)
Toll-like Receptor 4 (TLR4) induced pro-inflammatory signaling has been directly implicated in severe sepsis and represents an attractive therapeutic target. Herein, we report our investigations into the structure-activity relationship and preliminary drug metabolism/pharmacokinetics study of β-amino alcohol derivatives that inhibit the TLR4 signaling pathway. Lead compounds were identified from in vitro cellular examination with µM potency for their inhibitory effects on TLR4 signaling and subsequently assessed for their ability to suppress the TLR4-induced inflammatory response in an ex vivo whole blood model. In addition the toxicology, specificity, solubility, brain-blood barrier permeability, and drug metabolism of several compounds were evaluated. Although further optimizations are needed, our findings lay the groundwork for the future drug development of this class of small molecule agents for the treatment of severe sepsis.